The Effect Of The Quality Of Human Resources On Community Satisfaction And Service Quality As An Intervening Variable In The Population And Civil Registration ServicesPinrang District - Yullang (Scientia Integritas Utama, 2022)
The quality of human resources and the quality of services received by the community are still classified as ineffective with the completion time of a file still experiencing delays to an unspecified time and a lack of confirmation to the community for the services provided so that community satisfaction is not fulfilled at the Pinrang district population and civil records service . This study uses a quantitative approach. This study aims to analyze (1) the effect of the quality of human resources on community satisfaction (2) the effect of the quality of human resources on service quality, (3) the effect of service quality on community satisfaction, (4) the effect of the quality of human resources on community satisfaction through service quality. The research population totaled 407,371 people with a sample of 100 respondents using a side random technique. The data analysis method used is path analysis and Sobel test to determine the indirect effect of variables. The results showed that the quality of human resources had a positive and significant effect on community satisfaction and service quality, service quality had a positive and significant effect on community satisfaction, and the quality of human resources had an indirect, positive and significant effect on society through service quality with test results sobel of 6,464 < 1.96 (absolute value Z). The higher the quality of human resources, the better the quality of service that can increase community satisfaction.